Upaya Menanamkan Nilai Moral Pada Anak Usia Dini Usia 5-6 Tahun Melalui Penerapan Game Edukasi Berbasis Wordwall di Tk Al-Falah - Muthi’ah Munadiya; Redi Awal Maulana; Elnawati (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This research aims to instill moral values in early childhood through the application of Wordwall-based educational games at Al-Falah Kindergarten. Moral values are an important aspect in the development of children's character from an early age, because they are the foundation in the formation of personality and social behavior in the future. The method used in this study is Classroom Action Research (PTK) with the research subjects of group B children aged 5-6 years. The research was carried out in two cycles, each consisting of the stages of planning, implementation of actions, observation, and reflection. The instruments used included observation sheets, interviews, and documentation. The results of the study show that the application of Wordwall-based educational games can increase the understanding and practice of moral values such as honesty, responsibility, cooperation, and respect for others. Interactive and fun activities in games help children more easily understand moral concepts and apply them in daily life. Thus, Wordwall has proven to be an effective and innovative medium in instilling moral values in early childhood.